Student Teachers’ Verbal and Nonverbal Communication in EFL Class at MAN 2 Makassar - Nurdiana Nurdiana; La Sunra; Chairil Anwar Korompot (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The method used in this research is the descriptive qualitative method with a sample of 6 student teachers divided into teams. Each team has two students in the class. Class 10 MIPA 6 consisted of 29 students, and Class 10 IKA consisted of 32 students. The researchers analyzed five videos of teaching and learning sessions. The researchers observed and recorded the teaching and learning activities at MAN 2 Makassar through the Ajarmi program. While the student teachers Ajarmi teach, they record their lessons on video. After observation, the researchers watched the video and then transcribed the video. Then, the researchers analyzed and then classified in the form of communication both verbal and nonverbal communication. The researchers found four types of verbal communication used by student teachers in the classroom, there are intrapersonal communication, interpersonal communication, public communication and small group communication. Meanwhile, there are three types of verbal communication used by student teachers in the classroom, there are kinesics, proxemics and facial expression. So, it can be concluded that the most frequently used by student teachers is public communication the types of verbal communication because student teachers always involve all students in the learning process so that they know the increase in students’ knowledge in EFL class.